Chronic Pain in Breast Cancer Survivors: Nociceptive, Neuropathic, or Central Sensitization Pain?. Issue 2 (15th November 2018) - Leysen, Laurence; Adriaenssens, Nele; Nijs, Jo; Pas, Roselien; Bilterys, Thomas; Vermeir, Sofie; Lahousse, Astrid; Beckwée, David
Abstract: Introduction: The differentiation between acute and chronic pain can be insufficient for appropriate pain management. The aim of this study was to evaluate the prevalence of the predominant pain type (nociceptive, neuropathic, or central sensitization [CS] pain) in breast cancer survivors (BCS) with chronic pain. The secondary aims were to examine (1) differences in health‐related quality of life (HRQoL) between the different pain groups; and (2) the associations between patient‐, disease‐, and treatment‐related factors and the different pain types. Methods: To determine the prevalence of the predominant type of pain, a recently proposed classification system was used. BCS were asked to complete the VAS for pain, Douleur Neuropathique 4 Questionnaire, Margolis Pain Diagram, Central Sensitization Inventory, and Short Form 36 (SF‐36). Results: Ninety‐one BCS participated, among whom 25.3% presented neuropathic pain, 18.7% nociceptive pain, and 15.4% CS pain. Mixed pain was found in 40.6%. A significant intergroup difference in HRQoL was found for SF‐36 "general health" ( P = 0.04). The odds for the presence of CS rather than nociceptive pain are 26 times higher in patients exposed to hormone therapy in comparison to the nonexposed (odds ratio 25.95, 95% confidence interval 1.33 to 504.37, P = 0.03). Conclusion: Neuropathic pain is most frequent in BCS. Strong associations were found between CS pain and hormone therapy.